Queer Masculinities, 1550-1800
XXIX, 257 p.
Keywords: This book offers the most up to the minute snapshot of scholarship on queer/gay historiographies in a number of geographical regions in western Europe, Asia and the US. It features the work of the most established scholars in the field of the history of same-sex desire and promises to take the study of same-sex relations in the early modern period in radical new directions.